(untitled) (SCIENCE TIME JOURNAL, 2026)
English for Specific Purposes (ESP) has become an essential component of higher education, particularly for non-English major students who require specialized language skills for academic and professional contexts. However, teaching ESP presents numerous challenges for both instructors and learners. This study investigates the key difficulties encountered in ESP instruction for non-English major students, focusing on issues such as low language proficiency, lack of motivation, insufficient teaching materials, and limited subject-matter knowledge among instructors. Using a qualitative research design, data were collected through literature review and analysis of previous empirical studies. The findings reveal that effective ESP teaching requires a balance between linguistic competence and domain-specific knowledge, as well as the integration of innovative teaching methods. The study concludes with pedagogical recommendations aimed at improving ESP instruction and enhancing student learning outcomes.